Reconceptualizing the dark ride experience using first-hand experience: Including the visitor's perspective - Pieter C. M. Cornelis; Wim Strijbosch (Annals of Tourism Research Empirical Insights, 2024)
Dark rides embody a noteworthy phenomenon in theme park destinations and beyond, serving as a textbook example of structured experiences. They therefore offer valuable insights for knowledge development on structured experiences in the broader realm of tourism and leisure experiences. Despite various conceptualizations of the dark ride experience, the visitor's perspective has been largely overseen. Through qualitative interviews we explored 16 distinct dark rides, unveiling key constituent components of their experience and identifying contributing factors. Results indicate that dark rides are primarily appreciated for their ability to generate here-and-now experiences, characterized by imagery, imagery-based states, and emotions. However, visitors may inadvertently shift their focus to internal thoughts and cognitions based on motivation, opportunity, and ability-related switch factors, risking mental disengagement.
Keywords: 330; Dark rides; Emotion; Experience; Imagery; Immersion; Theme parks